Influence of Confined Acoustic Phonons on the Nonlinear Acousto-electric Effect in Doped Semiconductor Superlattices - Quyet Thang, Nguyen; Dinh Nam, Nguyen; Bau, Nguyen Quang (VNU Journal of Science: Mathematics - Physics; Vol 35 No 2DO - 10.25073/2588-1124/vnumap.4339, 2019)
Abstract: By using a quantum kinetic equation for electrons, we have studied the Acousto-electric effects in doped semiconductor superlattice (DSSL) under the influence of confined phonon. Considering the case of the electron - acoustic phonon interaction, we have found the expressions of the nonlinear quantum acousto-electric current. From these expression, the acousto-electric current (AEC) depends nonlinearly on temperature, acoustic wave frequency and the characteristic parameters of DSSL (For example: the doped concentration ). Moreover, the expression of the AEC under the influence of confined phonons fairly different from the case of unconfined phonons. The results are numerically calculated for the GaAs:Be/ GaAs:Si DSSL; therefore, it can be easily seen that the dependence of the acousto-electric current on the characteristic parameters of the acoustic wave, temperature, the characteristic parameters of DSSL and the quantum number m characterizing the phonons confinement. The results have showed that the appearance of phonons confinement make the AEC value changes remarkably. The AEC is almost stable in low acoustic wave frequency condition and changes as a parabolic curve when  move up. On the other hand, in case of low doped concentration number the AEC surges as a parabolic function in the dependence on , then it remains stability at just below zero in high  value. Keywords: Acousto-electric field, Quantum kinetic equation, Doped superlattices, Electron - phonon interaction. References [1] A. Wixforth, W. Schlapp, Surface acoustic waves on GaAs/AlxGa1−xAs heterostructures, Phys. Rev. B40 (1989) 7874. [2] R.L. Willett, R.R. Ruel, K.W. West, Experimental demonstration of a Fermi surface at one-half filling of the lowest Landau level, Phys. Rev. Lett. 71 (1993) 3846. [3] S.Y. Mensah, F.K.A. Allotey and N.G. Mensah, Nonlinear acoustoelectric effect in a semiconductor superlattice, Journal of Physics: Condensed Matter 12 (24) (2000), 5225 – 5232. [4] R.L. Willet, M.A. Paalanen, R.R. Ruel, Anomalous sound propagation at ν=1/2 in a 2D electron gas: Observation of a spontaneously broken translational symmetry, Phys. Rev. Lett. 65 (1990) 112. [5] J.M. Shilton, D.R. Mace, V.I. Talyanskii, Effect of spatial dispersion on acoustoelectric current in a high-mobility two-dimensional electron gas, Phys. Rev. B51 (1995) 14770. [6] V.I. Talyanskii, M. Pepper, J.M. Shilton, Single-electron transport in a one-dimensional channel by high-frequency surface acoustic waves, Phys. Rev. B56 (1997) 15180. [7] P. Das, R.T. Webster, H. Estrada-Varquez, W.C. Wang, Contactless semiconductor surface characterization using surface acoustic waves, Surf. Sci. 86 (1979) 848. [8] J.M. Shilton, D.R. Mace, V.I. Talyanskii, M.Y. Simmons, M. Pepper, A.C. Churchill, D.A. Ritchie, Effect of spatial dispersion on acoustoelectric current in a high-mobility two-dimensional electron gas, Physical Review B 51( 20) (1995) 14770. [9] J.M. Shilton, D.R. Mace, V.I. Talyanskii, On the acoustoelectric current in a one-dimensional channel, J. Phys:Condens. Matter.8 (1996) 337. [10] O.E. Wohlman, Y. Levinson, Yu. M. Galperin, Acoustoelectric effect in a finite-length ballistic quantum channel, Phys. Rev. B62 (2000) 7283. [11] N.A. Zimbovskaya, G. Gumbs, The effect of a magnetic field on the acoustoelectric current in a narrow channel, J. Phys: Condens. Matter. 13 (2001) 409. [12] J. Cunningham, M. Pepper, V.I. Talyanskii, Acoustoelectric current in submicron-separated quantum wires, Appl.Phys.Lett. 86 (2005) 152105. [13] B. Reulet, A.Yu. Kasumov, M. Kociak, Acoustoelectric Effects in Carbon Nanotubes, Appl. Phys. Lett. 85 (2000) 2829. [14] M.R. Astley, M. Kataoka, C. Ford, Quantized acoustoelectric current in an InGaAs quantum well, J. Appl. Phys. 103 (2008) 096102. [15] N.Q. Bau, D.M. Hung, L.T. Hung, The Influences of Confined Phonons on the Nonlinear Absorption Coefficient of a Strong Electromagnetic Wave by Confined Electrons in Doping Superlattices, Progress In Electromagnetics Research Letters 15 (2010) 175-185.